PERANAN DEWAN KEAMANAN PERSERIKATAN BANGSA-BANGSA DALAM PROSES PENYELESAIAN KONFLIK INTERNASIONAL - Danial . (Jurnal Ilmu dan Budaya, 2010)
In particular, to solve the international conflicts, the Security Council of the United Nations takes two steps; peaceful or compulsive way. It is such reformation to eliminate the veto of constant Council of the United Nations by normative juridical methods.